Biochemical Composition and Isoenzymes of Enzyme Peroxidase of Houttuynia Cordata Thunb. from Brahmaputra Valley of Assam, India - Bhattacharyya, N.; Sarma, S. (International Journal of Bio-resource and Stress Management, 2017)
Houttuynia cordata Thunb. is a medicinal herb under the family Saururaceae, distributed in South-East Asia, mainly in China, Japan, Thailand and North-East India. In the present study, percentage of total chlorophyll, carotene and extractable essential oil were estimated in active growing season (April to July in 2008) in five different populations i.e. Nalbari (NL), Guwahati (GH), Nagaon (NG), Jorhat (JR) and Dhemaji (DH) in the Brahmaputra valley of Assam. Average percentage of total chlorophyll, carotene and extractable essential oil were found to be 1.77%, 3.0% and 0.065% respectively. The simple linear curve fit of EO (%) with chlorophyll (%) and carotene (%) had shown that the EO (%) could be significantly related to the lowest chlorophyll (%) and the highest carotenoid (%) in the samples. A total of 28 components were identified by GC-MS analysis and the percentage of methyl nonyl ketone was the highest in all the five populations (33.722±1.261). Isoenzymes of enzyme peroxidase, present in H. cordata were studied to know the molecular identity of the herb in the valley. The total numbers of isoenzymes were found to be six, which was comparable with that of Sichuan, China. There is no geographical variance, at least regarding the number of peroxidase isozymes present, in the H. cordata plants collected from Jorhat district of Assam, North East India and that of Sichuan, China.